(untitled) (Journal of actual problems of jurisprudence, 2019)
The subject of private enterprise in the performance of registration, control functions and other actions Kazakhstan, state bodies and officials, actions under To carry out the functions assigned to them, established by the laws of the Republic of Kazakhstan do not provide information protected by trade secrets, except the necessary information.